REPORTING INFORMATION SYSTEM OF PLANTATION PRODUCTS IN THE DEPARTMENT OF FOOD, HORTICULTURE AND PLANTATION - Fitria Aliarti; siti Ramadhani (UIN Sultan Syarif Kasim Riau, 2020)
The Food Crops, Horticulture and Plantation Office is an agency that handles the plantation sector and becomes a facilitator in the availability of facilities and infrastructure. Good service and development to get maximum yields. The harvest data collection is still done manually by bookkeeping. The yield data that will be sent from the sub-district to the district can be said to be inefficient because in storing data manually there are many risks such as loss or damage. Storing the recap of harvest data in a book takes quite a long time. Seeing the problems that occur then with the report input facilities and print reports contained in the Plantation Product Reporting Information System at the Office of Food Crops, Horticulture and Plantations can facilitate the process of inputting the yields of sub-districts. The results of the UAT that have been done show that the system interface is good enough, in terms of ease of use the system gets a good response from users and in terms of system functions show the results that the system has been functioning according to user needs. This system was built using waterfall development techniques and using the PHP programming language and using the MYSQL database. Keywords: Harvest Results, Regency, District, Plantation, Information System.